Recycled lives: a history of reincarnation in Blavatsky's theosophy - Chajes, Julie (Oxford studies in Western esotericism, 2019)
A sizeable minority of people with no particular connection to Eastern religions believe in reincarnation. The rise in popularity of this belief over the last century and a half is the direct result of the impact of the nineteenth-century's largest and most influential Western esoteric movement, the Theosophical Society. In Recycled Lives, Julie Chajes explains and historicises the rebirth doctrines of the matriarch of Theosophy, the controversial occultist, Helena Petrovna Blavatsky (1831-1891). Examining her teachings in detail, Chajes contextualises them in light of multiple dimensions of nineteenth-century intellectual and cultural life. In particular, this book explores Blavatsky's readings (and misreadings) of Spiritualist currents, scientific theories, Platonism, and Hindu and Buddhist thought. These, in turn, are set in relief against broader nineteenth-century American and European trends. The chapters come together to reveal the contours of a modern perspective on reincarnation that is inseparable from the nineteenth-century discourses within which it emerged, and which has shaped how people in the West tend to view reincarnation today